Asam Lemak Hidroksamat: Sifat Kimia dan Aplikasinya dalam Bidang Bioteknologi - Muhsinun, Muhsinun (Lembaga Publikasi Ilmiah Nusantara, 2025)
Fatty hydroxamic acids are chemical derivatives formed through the modification of the carboxyl group of fatty acids into a hydroxamate group, imparting unique and functional properties. The key chemical properties of these compounds include the ability to form strong complexes with metal ions, act as antioxidants, and possess high thermal and chemical stability. These combined properties make hydroxamate fatty acids relevant for various applications in the field of biotechnology. In waste treatment, these compounds serve as chelating agents to selectively bind heavy metals. In the pharmaceutical and food industries, hydroxamate fatty acids show potential as antimicrobial agents and natural preservatives. Furthermore, these compounds are used in enzymatic engineering to enhance the efficiency of biocatalytic reactions. Recent research also explores their use in microbial metabolic engineering to produce bioactive compounds with high added value. This article provides an in-depth review of the chemical properties, mechanisms of action, and diverse innovative applications of hydroxamate fatty acids, as well as discusses the technical challenges and opportunities for further development in the modern biotechnology era.